HAKIM DALAM TELAAH KONSEP PROFETIK DAN SISTEM HUKUM, L.W FRIEDMAN - Firmansyah, Firmansyah (Al AHKAM: Jurnal Kajian Ilmu Hukum dan Syariah, 2015)
To birth to the norm in this case is the decision of the judge with justice it must beunderpinned by the values that are understood and adhered to by the judges that the ideologythat birth to a norm or a decision , where the values are believed to be the prophetic value thatis therein included the value of Transcendence , humanist and the liberation it is also consistentwith the view LW Friedman with a legal system that consists of a substance , structure andculture.